Advances in accounting behavioural research. Vol. 16 - Schmitt, Donna Bobek (Emerald, 2013)
Volume 16 exemplifies this focus by including nine different chapters spanning topics such as auditor liability, ethical decision-making of accounting professionals, taxpayers' perceptions of tax policy, and the effect of auditor changes on commercial lenders' decision-making. The first three chapters focus on liability effects of accounting information: the effect of web disclosure of environmental information on liability assessments, the effect of identifying and investigating fraud risks on assessments of auditor liability, and the effect of offshoring audit tasks on assessments of auditor liability. The next four chapters relate to ethical aspects of judgment and decision-making: the influence of peer honesty in a managerial accounting setting, the influence of individual characteristics in a financial accounting setting, the influence of moral reasoning in a tax setting, and the relationship between political ideology and moral reasoning of accounting professionals. The next chapter investigates taxpayers' perceptions related to innocent spouse provisions and the final chapter considers the role of auditor changes on commercial lenders' decisions to extend credit.
Keywords: Accounting -- Psychological aspects -- Research.; Accounting -- Moral and ethical aspects.; elektronické knihy; electronic books